Computational Analysis of Closed Cycle Magneto Hydro Dynamics Power Plant with Liquid Metal as Heat Source - Pitchaipillai, A.; Kanimozhi Vendhan, G.; Ananth Vino, V. Jose (International Journal of Psychosocial Rehabilitation, 2019)
The increase in high demand of coal with the growing industrial power requirements and necessary to control the emission level in the atmosphere, we need to search for an alternate heat source to drive the modern power plant. Magneto Hydro Dynamic power generation is a non-conventional method in the modern system in which there is no rotating turbine and conventional conductor are used. Argon gas behaves as conductor at its elevated temperature in the ionized plasma condition with the strong influence of magnetic field placed over the CD duct. The positive and negative ions are collected by electrode which are DC in nature, can be converted to AC by an invertor. In the metallurgical industry like Aluminium production, the waste heat recovered from liquid aluminium through a heat exchanger as a heat source to heat the inert gas or argon gas to its plasma range in the MHD. By seeding the plasma gas with alkaline metal like potassium or cessium, the conductivity can be increased. The generated power can be used within the metallurgical industry independently rather than depending on commercial power source, by the characteristics of liquid metal in improved thermal conductivity and flow characteristics.